Metode Permainan Berbantuan Bingo Edukasi dalam Mewujudkan Pembelajaran Bermakna pada Mata Pelajaran Pendidikan Pancasila - Eka Widiarti, Anisah; Kurnisar (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to determine the effect of implementing game-based learning methods on the realization of meaningful learning in Pancasila Education at SMAN 1 Martapura. The research employed a quantitative approach with a quasi-experimental method, specifically the non-equivalent group design. The population consisted of 358 tenth-grade students, with samples selected through purposive sampling. Class XC was designated as the experimental group, receiving treatment using the "Educational Bingo" media, while class XE served as the control group. Data were collected through documentation, cognitive tests, and questionnaires. The data analysis, conducted using the independent sample t-test, showed a significance value (sig. 2-tailed) of <.001 for the test instrument and 0.049 for the questionnaire. Given that both significance values were less than 0.05, the null hypothesis H0 was rejected, and the alternative hypothesis Ha was accepted. Therefore, it is concluded that the application of the game-based method using Educational Bingo has a significant influence on the realization of meaningful learning in Pancasila Education at SMAN 1 Martapura. This impact is evidenced by an increase in students' cognitive understanding in the experimental class, with an average pre-test to post-test improvement, and increase in non-cognitive aspects based on the questionnaire data.